15.8% efficiency all-small-molecule solar cells enabled by a combination of side-chain engineering and polymer additive. Issue 20 (5th May 2022) - Liang, Haiyan; Wang, Yang; Guo, Xia; Yang, Ding; Xia, Xinxin; Wang, Jianqiu; Zhang, Liu; Shi, Yu; Lu, Xinhui; Zhang, Maojie
Abstract : BTR-SCl:Y6 devices achieved an impressive PCE of 15.8% with a high V oc of 0.88 eV. Abstract : All-small-molecule OSCs (ASM-OSCs) are more suitable for commercial-scale manufacturing owing to the merits of small molecules, such as well-defined chemical molecular structures, easy synthesis, and less batch-to-batch variation. With the rapid development of non-fullerene acceptors, the design of small molecule donors and the optimization of bulk heterojunction (BHJ) morphology will play a greater role in improving the power conversion efficiencies (PCE) of ASM-OSCs. Herein, a novel small molecule donor, BTR-SCl, with alkylthio and chlorine substituents on the side-chains was designed and synthesized. BTR-SCl exhibits strong absorption in the wavelength range of 400–700 nm with a wide optical bandgap of 1.77 eV, a low-lying highest occupied molecular orbital (HOMO) energy level of −5.51 eV, and strong crystallization properties. Consequently, a PCE of 14.6% was obtained from BTR-SCl:Y6 solar cells with a V oc of 0.88 V, a J sc of 23.4 mA cm −2, and an FF of 70.8%. Notably, with the incorporation of polymer PM7 as a morphology modulator, the BTR-SCl:Y6 matrix achieved well-formed bicontinuous interpenetrating networks and ordered molecular packing. As a result, PM7-optimized devices achieved a significantly enhanced PCE of 15.8% with a higher J sc of 24.5 mA cm −2 and FF of 73.1%.